Utilization of Reading Literacy Carts (GELISBA) to Interest in Reading to Support the MBKM Program at Bunda Pusaka Preschool - Makhroji Makhroji; Irma Dewi Isda; Sukirno Sukirno (Pascasarjana Universitas Mataram, 2023)
Reading as a skill views the nature of reading as a process or activity that applies a set of skills in managing what is read that captures meaning. Developed countries are countries where people's interest in reading is high. Therefore, interest in reading occupies an important position for the progress of a nation. Therefore, in order to increase the reading interest of students at the Early Childhood and Kindergarten levels in Sungai Pauh Pusaka even better, we are holding a work program that is an urgency for PKM activities in the form of procuring Reading Carts which we call Reading Literacy Carts (GELISBA). The objectives in community service activities are as follows: (a) Helping to increase public knowledge by reading various useful information; (b) Helps increase a person's level of understanding in drawing conclusions from the information read; (c) Improve a person's ability to provide critical assessment of a written work; (d) Helping to grow and develop good character within a person; (e) Increasing the value of one's personality through reading and writing activities (f) Fostering and developing a culture of literacy in the midst of society at large; (g) Helps improve the quality of one's time use so that it is more useful. The method of service activities uses the observation method or direct observation. Results of service activities This positively impacts teachers and students who can utilize the Reading Literacy Cart (GELISBA) as a learning medium